A framework for measuring sharia-compliant e-commerce success of halal companies in Malaysia - Mariana, Jusop (2022)
The advancement of technology has accelerated the growth of online businesses, also known as e-commerce. To ensure the authenticity of halal transactions, it is critical for the halal industry that platforms offering halal products adhere to sharia practices. This study aims to develop a framework for measuring sharia-compliant e-commerce success by identifying the criteria of information quality, system quality, and service quality using the well-established DeLone and McLean IS Success Model and exploring how halal e-commerce companies managed these quality aspects in the context of sharia business practice. Qualitative multiple case studies were carried out with four halal e-commerce companies in Malaysia and data were gathered through face-to-face semi-structured interviews. This study focused on top managers’ perspectives instead of consumers’ views about e-commerce success measures. This study developed a framework for measuring sharia compliance e-commerce success based on the input from literature and the semi-structured interviews, which were then validated by experts in the field of sharia and e-commerce to further enhance its pertinence to the industry. The findings revealed that information quality criteria include reliability, verification, clarity, format/presentation, timeliness, and completeness; system quality criteria include user-friendliness, integration, availability, and adaptability; and service quality criteria include assurance, responsiveness, empathy, and trusted delivery. Furthermore, the study discovered that halal logistics, Islamic business ethics, trust, and halalan-toyyiban were important factors in determining halal companies' sharia-compliant e-commerce success in Malaysia. This study contributes to the existing literature on IS success by developing a framework that integrates the e-commerce success model and sharia-compliant management practices in halal business. The study also provides guidelines for the government, halal authorities, and halal e-commerce providers to implement more effective strategies and governance in order to achieve successful sharia-compliant ecommerce uptake in the country. The limitations and future research directions are also presented.